Test of Acceptance and Iron Content of Baymor “Red Spinach & Moringa” as a Treat to Prevent Anemia in Adolescent Women - Anisah Rona Rosyidah; Juliana Christiyaningsih; Nuning Marina Pengge; Nur Hatijah (Journal of Nutrition Explorations, 2023)
Based on DP3AK 2021 East Java, 23% of young women and 12% of young men suffer from anemia. Red spinach and Moringa leaves are contain high levels of iron so it can be used as alternative foods to prevent anemia in young women. The purpose was to analyze the results of tests of acceptability and iron levels of "red spinach & moringa" baymor cake as a snack to prevent anemia in young women. The research method is experimental research. Data will be analyzed using the Kruskal Wallis test, if the results are p <0.05 then it will be continued using the Mann Whitney test. The average result of the acceptability test is the BM 1 formulation which is 4.04 (likes it), BM 2 which is 3.49 (rather likes it) and BM 3 which is 3.2 (rather likes it). The results of iron levels in the control formulation (BM 1) were 3.63 mg/100g and the most preferred formulation was BM 2 of 9.81 mg/100g. The control formulation (BM 1) with iron content of 3.63 mg/100g was the most preferred formulation by the panelists, while the second most preferred formulation was BM 2 of 9.81 mg/100g.